LATTICE BOLTZMANN PSEUDO-POTENTIAL MODELLING OF MULTIPHASE DROPLET PHENOMENA - Thomas Ken Darmastono; Bahrul Jalaali (Institut Teknologi Dirgantara Adisutjipto, 2020)
The multiphase modeling of a droplet in a multiphase system is considered becoming a fundamental problem in fluid dynamics. A complex understanding of droplet behavior is critical to reveal a deeper insight into a more complex multiphase system. Droplet behavior studies are necessary to obtain a better understanding of solving multiphase problems in both the science and industrial aspect. The droplet behavior is characterized by a non-dimensional number such as the Eötvös number. In this study, numerical simulation was performed using the Lattice Boltzmann method. Parametric studies of Eötvös number was done. The parametric study of the Eo number is obtained using LBM. Based on the results obtained, it is concluded that the gravitational force influences the downwards rate of the droplet. Furthermore, the shape of the droplet during falling was depended on the Eo number as well. The higher Eo number means higher gravitational force, hence the velocity of the droplet is increasing as well as the reaction force of surface tension. This study is beneficial to give a deeper explanation of multiphase phenomena as well as contribute to the modeling of multiphase phenomena using an alternative numerical method of LBM.